Mechanistic insights into the diuretic activity of sugarcane leaf extract using untargeted metabolomics and bioinformatics - Pan, Xianglong; Hao, Erwei; Xie, Jinling; Tang, Pei Ling; Wen, Juan; Du, Zhengcai; Deng, Jiagang; Hou, Xiaotao (Frontiers in Plant Science, 2025)
IntroductionSugarcane leaf (Poaceae) is a widely cultivated herbaceous plant in the tropical regions of southern China. Traditional Yao medicine has utilized its significant diuretic effects for the treatment of edema-related diseases. However, the underlying mechanisms of its diuretic activity remain unclear.MethodsThis study aims to elucidate the potential mechanisms of the diuretic activity of sugarcane leaf extract using untargeted metabolomics, network pharmacology, and molecular dynamics simulations.Results and discussionA water-loaded rat model was established to assess diuresis, and sugarcane leaf extract markedly increased urinary excretion of Na+, Cl-, and other ions. Ultra-performance liquid chromatography–mass spectrometry (UPLC–MS) identified ten absorbed constituents in rat serum after sugarcane leaf extract administration. Untargeted metabolomics revealed ten endogenous differential metabolites and two key metabolic pathways modulated by sugarcane leaf extract. Network pharmacology uncovered 63 overlapping targets, among which AKT1, IL-6, TNF, STAT3, and EGFR were pinpointed as core targets implicated in the diuretic response. Molecular docking and dynamics simulations confirmed strong binding affinities between these core targets and five absorbed sugarcane leaf extract constituents. The alanine, aspartate, and glutamate metabolism pathway was highlighted as pivotal for sugarcane leaf extract-induced diuresis. Collectively, this study has elucidated the diuretic mechanism of sugarcane leaf extract, providing a scientific basis for its clinical application and the development of novel diuretic agents.